THE ANALYSIS CONTEXTUAL TEACHING AND LEARNING MODEL TO IMPROVE ECOLITERACY CHARACTER OF STUDENTS IN GRADE 3 ELEMENTARY SCHOOL EDUCATION - Fitri Asylah, Lutfi; Agustin, Mubiar; Anjani, Cusni (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Education is one of the learning processes carried out by everyone, education can prepare the younger generation for life in the future. Education can adjust to the era of globalization. Education there are various aspects such as Cognitive, Affective and Psychomotor. This article aims to discuss the application of the Contextual Teaching and Learning model of ecoliteracy character in grade 3 elementary school students. The research method used is a literature study to describe the application of the Contextual Teaching and Learning model in ecoliteracy character education based on experts and based on supporting reference studies. The focus of this research is the application of the Contextual Teaching and Learning Model to foster the character of ecoliteracy in elementary school students. In this model helps students in finding opportunities to gain knowledge through life in the real world in the surrounding environment to the learning that students get. then things obtained by students can be discussed together in class. So the Contextual Teaching and Learning learning model allows students to have the opportunity to apply ecoliteracy character education in learning and in everyday life.